FAKTOR-FAKTOR YANG MEMENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI BEI - Siska Nathalia; Sufiyati Sufiyati (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
This research aims to find the effect of the independent variable which is firm size, profitability, financial leverage, institutional ownership, and cash holding on dependent variable, income smoothing in manufacture companies listed in the Indonesian Stock Exchange during 2017-2019. Total samples used in this study is 201 samples that selected with purposive sampling method. Data processing techniques using logistic regression analysis with the help of EViews 11 and Microsoft Excel 365. The results of this study show that profitability has negative and significant influence towards income smoothing, firm size and financial leverage have negative and insignificant influence towards income smoothing, institutional ownership and cash holding have a positive and insignificant effect towards income smoothing. The implication of this study is investors need to consider another elements beside of net income when assessing a company.